Semantic and phonetic elements of chemistry terms in English-Chinese translation - Low, Fong Ling; Ang, Lay Hoon (Universiti Putra Malaysia Press, 2014)
Translation covers a variety of disciplines or fields, including politics, philosophy, economics, art, science and religion to name a few. When one comes across different languages with two distinct cultures, translation appears to be the most frequently practiced method to introduce a common novel term. This paper examines the translation from English into Chinese. The data for this study are the Chinese translation of 112 chemical elements from a periodic table. This study uses a qualitative descriptive approach to examine the grammatical features of Chinese translation of chemical elements from the semantic and phonological perspectives. The analysis of data revealed that the unique property of Chinese radicals has been fully utilised in the Chinese translation. Consequently, the semantic aspects of the chemical elements are well informed in the translation. On the other hand, the phonological elements in Chinese translation have been simplified and reduced to only one sound which is represented by only one character. The translation of chemical elements is considered unique, both semantically and phonologically, in achieving the equivalence in the Chinese language.